Association Between TNF-α-308, +489, −238 Polymorphism, and COPD Susceptibility: An Updated Meta-Analysis and Trial Sequential Analysis - Xia, Zhiyu; Wang, Yufei; Liu, Fu; Shu, Hongxin; Huang, Peng (Frontiers in Genetics, 2022)
Accumulated evidence has demonstrated that TNF-α polymorphism was associated with the Chronic obstructive pulmonary disease (COPD) susceptibility, among which +489G/A, -238G/A, -308G/A were widely studied. However, different conclusions were concluded. Hence, we performed a comprehensive search and finally pooled 27 original studies to obtain a more explicit understanding of the association between TNF-α+489G/A, -238G/A, and -308G/A polymorphism and susceptibility to COPD. Odds ratio (OR) and its 95% confidence interval (95%CI) were calculated to assess the association between TNF-α and COPD risk. Trial Sequential analysis (TSA) was also performed to confirm our results. Overall, association between TNF-α-308G/A polymorphism and susceptibility to COPD was identified in allelic model (OR=1.21, 95%CI:1.01-1.45, P=0.04), GA genotype carriers of TNF-α-308 have a higher risk of developing COPD compared to GG carriers (GA vs. GG, OR=1.22,95%CI:1.02-1.45, P=0.03;GA+AA vs. GG, OR=1.22, 95%CI:1.01-1.48, P=0.04).In subgroup analysis, the correlation of the polymorphism with COPD risk was found in Asians under the allelic model (A vs. G, OR=1.40,95%CI:1.03-1.89, P=0.03),heterozygote model (GA vs. GG, OR=1.35, 95%CI:1.04-1.77, P=0.02) and dominant model (GA+AA vs. GG, OR=1.40, 95%CI:1.04-1.88, P=0.03). The present meta-analysis indicated that TNF-α-308G/A polymorphism was associated with an increased risk of COPD among Asians but not in Caucasians, and GA genotype carriers of TNF-α-308 had a higher risk of developing COPD compared to GG carriers. However, In the meta-analysis with restrictions to smokers, no association was found between TNF-α-308G/A polymorphism and COPD susceptibility either in Asian smokers or Caucasian smokers. Moreover, the TNF-α+489G/A, -238G/A variants did not have an increased risk of COPD susceptibility.